Micro-cantilever flow sensor for small aircraft - Ghommem, M.; Calo, Victor; Claudel, C. (2015)
We extend the use of cantilever beams as flow sensors for small aircraft. As such, we propose a novel method to measure the airspeed and the angle of attack at which the air travels across a small flying vehicle. We measure beam deflections and extract information about the surrounding flow. Thus, we couple a nonlinear beam model with a potential flow simulator through a fluid-structure interaction scheme. We use this numerical approach to generate calibration curves that exhibit the trend for the variations of the limit cycle oscillations amplitudes of flexural and torsional vibrations with the air speed and the angle of attack, respectively.